Señalamos la importancia de la presencia de tejidos en los organismos - Hoyos Bustamante, José (2021)
This sufficiency work entitled "We point out the importance of the presence of tissues in organisms" integrates a learning experience oriented to the development of competence explains the physical world function in knowledge about living beings, matter and energy, biodiversity, earth and universe, from the area of science and technology for which it uses the elements and real cases oriented to the solution of problems, through methods such as Learning based on problems and techniques such as brainstorming and debate. The learning experience is supported by the theories that base the national curriculum of regular basic education, which guided the achievement of the fulfillment of the purpose.